Hepatocyte adhesion to carbohydrate-derivatized surfaces. I. Surface topography of the rat hepatic lectin (The Rockefeller University Press, 1991)
The rat hepatic lectins, galactose- and N-acetylgalactosamine-binding proteins found on the hepatocyte cell surface, mediate adhesion of isolated primary rat hepatocytes to artificial galactose-derivatized polyacrylamide gels. Biochemical and immunohistochemical techniques were used to examine the topographical redistribution of the rat hepatic lectins in response to galactose-mediated cell adhesion. Hepatocytes isolated from rat liver by collagenase perfusion had an average of 7 x 10(5) cell surface lectin molecules per cell, representing 30-50% of the total lectin molecules per cell, the remainder residing in intracellular pools. Hepatocytes incubated on galactose-derivatized surfaces, whether at 0-4 degrees C or 37 degrees C, rapidly lost greater than 80% of their accessible cell surface lectin binding sites into an adhesive patch of characteristic morphology. The kinetics of rat hepatic lectin disappearance were used to estimate a lateral diffusion coefficient greater than 9 x 10(-9) cm2/s at 37 degrees C, suggesting rapid and unimpeded lectin diffusion in the plane of the membrane. Indirect immunofluorescence labeling of adherent cells using antihepatic lectin antibody revealed a structured ring of receptors surrounding an area of exclusion (patch) of reproducible size and shape which represented approximately 8% of the hepatocyte cell surface. Notably, adherent cells, which had lost greater than 80% of their accessible surface binding sites, still endocytosed soluble galactose-terminated radioligand at greater than 50% of the rate of nonadherent control cells. No net movement of rat hepatic lectin from intracellular pools to the cell surface was found on cells recovered after adhesion to galactose-derivatized surfaces at 37 degrees C, suggesting that the physical size and/or lectin density of the patch was restricted by kinetic or topological constraints.